Low jitter parabolic profile low density plasma channel in 3D printed gas filled capillary. (28th June 2021) - Raz, Yoav; Behar, Ehud; Ferber, Yair; Biagioni, Angelo; Galletti, Mario; Pia Anania, Maria; Pompili, Riccardo; Gemma, Costa; Zigler, Arie
Abstract: A parabolic profile plasma channel formed by an electric discharge inside a gas filled capillary are currently used to achieve optimal conditions for laser guiding and electron acceleration. Acceleration of high quality externally injected electron beam by laser induced wake field requires precise synchronization between several systems. In our experiment the measured jitter in plasma ignition was on the scale of 1 ns, providing possibility for the synchronization with high intensity laser and other auxiliary systems (e.g injectors). We confirmed the existence of a parabolic density plasma profile inside the capillary using an 84 MHz oscillator laser and found its duration to be approximately 300 ns.